Edukasi Bahaya Rabies Melalui Media Komunikasi Bagi Siswa Sekolah Dasar Desa Tumbang Jalemu Kecamatan Manuhing Kabupaten Gunung Mas - Eshariyani Eshariyani (Jurnal Ilmiah Kanderang Tingang, 2024)
The aim of this research is to increase elementary school children's insight into the spread of rabies and diseases caused by bites from pets infected with rabies and to find out steps to prevent the transmission of rabies or what is known as animals that transmit rabies to humans. Education activities regarding the dangers of rabies were carried out in Tumbang Jalemu Village, Manuhin District, Gunung Mas Regency, Central Kalimantan. Methods include: counseling, discussions and questions and answers, distributing posters and distributing rabies danger stickers. The results of the first research, through information, educate elementary school students to be more aware of the dangers of the rabies virus which is transmitted through pets, especially dogs; secondly, students, teachers and parents are motivated to prevent transmission from the saliva of animals infected with the rabies virus, considering the importance of health for children; third, with this extension activity, elementary school students receive information about the dangers of the rabies virus, and learn about the characteristics of animals infected with rabies, and steps to handle if they are bitten so they don't contract rabies.